Fabrician types of new world Oedionychina Chapuis, 1875 (Coleoptera, Chrysomelidae, Alticini) deposited in the Zoological Museum of Kiel University collections with notes on Fabrician types of other collections and new combinations for species formerly pl - Martijn Van Roie; Michael Kuhlmann; Anne Mack; Alexander Konstantinov (European Journal of Taxonomy, 2024)
Type specimens of Oedionychina Chapuis, 1875 described by Fabricius from the Kiel collection are examined and illustrated. Lectotypes are designated for the following species: Chrysomela albicollis Fabricius, 1787; Chrysomela nobilitata Fabricius, 1787; Chrysomela quadrifasciata Fabricius, 1787; Chrysomela quadriguttata Fabricius, 1781; Galleruca atomaria Fabricius, 1801; Galleruca decemguttata Fabricius, 1801; Galleruca fasciata Fabricius, 1798; Galleruca humeralis Fabricius, 1801; Galleruca lunata Fabricius, 1801; Galleruca nitida Fabricius, 1801; Galleruca obsoleta Fabricius, 1801; Galleruca petaurista Fabricius, 1801; Galleruca quadrinotata Fabricius, 1798; Galleruca sellata Fabricius, 1801. The species status is restored for Chrysomela quadriguttata Fabricius, 1781 and Alagoasa areata (Germar, 1824) comb. nov. The following new combinations are proposed: Phenrica quadriguttata (Fabricius, 1781), Asphaera nitida (Fabricius, 1801), Phenrica obsoleta (Fabricius, 1801), Alagoasa areata areata (Germar, 1824), Alagoasa areata decempunctata (Latreille, 1833), Alagoasa areata escuintla Bechyné, 1955, Alagoasa areata macromela Bechyné, 1958, Alagoasa areata praecessa Bechyné, 1959, Alagoasa areata recuperata Bechyné, 1959; all comb. nov. New placement: Galleruca avicenniae Fabricius, 1792 is removed from Alticini and placed in Galerucini incertae sedis; Galleruca trifasciata Fabricius, 1801 is removed from Chrysomelidae and placed in genus Ora Clark, 1865 (Scirtidae Fleming, 1821).